(untitled) (Tanzania Medical Journal, 2023)
Background Asymptomatic bacteriuria (ASB) in pregnancy is associated with poor fetal and maternal outcomes. Treatment of ASB in pregnant women is of great concern due to the emergence of antimicrobial resistance. In this study, we determined the prevalence of ASB, bacterial profile, and antimicrobial susceptibility pattern among pregnant women attending an antenatal clinic (ANC) at a secondary-level hospital. Methods A cross-sectional study was conducted among pregnant women attending ANC at Sinza District Hospital. A total of 329 pregnant women with no symptoms of urinary tract infection were recruited from November 2019 to January 2020. A structured questionnaire was used to collect sociodemographic and obstetric information of pregnant women following health education session where a minimum of ten pregnant women were enrolled into the study daily. Clean catch mid-stream urine samples were collected from all study participants using sterile containers and transported in an ice-packed cool box to Microbiology laboratory at Muhimbili University of Heath and Allied Sciences for processing. Urinalysis using urine dipstick, urine culture, and antimicrobial susceptibility testing were performed. Bacterial identification was done based on colonial morphological and biochemical tests. Data was analyzed for frequency distribution, proportions and proportional differences using the Chi-square test. Results Out of 320 pregnant women included in the final analysis, 21 (6.6%) were diagnosed with ASB. Nine samples were excluded from the analysis due to fungal or mixed growth. E. coli was the predominant isolate 9/21(42.8%), followed by Staphylococci spp 4/21 (19.0%). Among the gram-negative isolates, E. coli demonstrated a high resistance rate to amoxicillin (89%), amoxicillin-clavulanic acid (89.0%), and trimethoprim/sulphamethoxazole (78.0%) but susceptible (100.0%) to amikacin, gentamycin, nitrofurantoin, and meropenem. All enterococci spp were resistant to trimethoprim/sulphamethoxazole and 66.6% to nitrofurantoin while Staphylococci spp showed 50% resistance. The urine dipstick test showed a sensitivity of 38.1 %, specificity (93.3%), positive predictive value (28.6%) and negative predictive value (95.6%) respectively. Conclusion The prevalence of ASB among pregnant women attending ANC at secondary-level hospital was lower than previous findings in Tanzania. Escherichia coli was the most isolated organism causing ASB. High rate of resistance was observed to commonly prescribed antibiotics. Urinalysis revealed high false positive results. We recommend large study to be conducted involving secondary level facilities in order to gather enough data on AST pattern as well as to guide patient’s management.